Entwicklung von Siebdruckpasten zur Herstellung von Glaslotfügungen für die Festoxidbrennstoffzelle - Dittrich, Svenja (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2021)
Solid oxide fuel cells are used to generate electricity from various fuel gases. The sealants between the stack-components should be gas-tight, mechanically stable and insulating. This work shows that glass ceramics can be used as sealant material for fuel cells. Solvent- and water-based suspensions are made from alkaline earth silicate glass and thick layers are produced using the screen-printing process. To demonstrate the applicability, they are soldered between steel and ceramic substrates.